A Proposal for Desert House Design in Egypt Using Passive Ground Cooling Techniques - Mohamed Medhat Dorra; Hend El-Sayed Farroh; Lubna Amer (Renewable Energy and Sustainable Development, 2018)
An area less than 5.5% of Egyptian territory is where most of Egypt‘s population lives in. A narrow strip of land forms the Nile Valley and Delta sector. The National Project for Desert Hinterlands is one of the urban projects targeting rehabilitation of the poor in alternative villages in the near desert to stop urban sprawl over agricultural land and decrease the congestion in the old habitats. Low cost energy efficient houses are the aim of the architect in similar projects taking in consideration the high electricity consumption of Egypt’s residential sector. Based on a literature review, this paper presents a proposal for designing desert dwellings that accommodates the hot dry climate by incorporating passive elements and using stabilized earth blocks as a local building material. Furthermore, simulation is used to test alternative proposals. The results show that an underground constructed house with a sunken courtyard incorporating an Earth to Air Heat Exchanger System (EAHE) can reduce between 42-72% of energy consumption used to achieve thermal comfort compared to contemporary desert housing projects.